2011
DOI: 10.1111/j.1755-6686.2011.00216.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Infection in Patients With Chronic Kidney Disease Part Ii: Healthcare‐associated Infections

Abstract: This second article, in a three-part CE series on the prevention of infection in patients with chronic kidney disease, focuses on healthcare-associated infections and blood borne viruses that are prevalent within the haemodialysis environment. It also informs the reader of the relevant infection and prevention precaution guidelines and their application within a haemodialysis setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In our study, SSI and HAP were the most common HAI types reported, which was similar to that reported in a systematic review and meta-analysis of HAI in developing countries 3 . As per other studies, the frequency of SSI varies between 1.2 and 5.2 per cent in high-income countries 10 19 29 . VAP was also reported by other authors with an alarming rate 30 31 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In our study, SSI and HAP were the most common HAI types reported, which was similar to that reported in a systematic review and meta-analysis of HAI in developing countries 3 . As per other studies, the frequency of SSI varies between 1.2 and 5.2 per cent in high-income countries 10 19 29 . VAP was also reported by other authors with an alarming rate 30 31 .…”
Section: Discussionsupporting
confidence: 72%
“…The odds of acquiring an HAI are 8.59 times more when a patient is exposed to central AC than other modalities of AC. Similarly, the odds were 4.20 times more when exposed to split AC ( Table II ) 8 9 10 11 . The association between AC and HAI was found significant ( P <0.05) for all the modalities of ventilation.…”
Section: Resultsmentioning
confidence: 93%